Building A Muslim Worldview Through Islamic Education in The Middle of Globalization - Arinal Husna; Yusqi Mahfuds; Yusuf Olawale Owa-Onire Uthman; Andika Aprilianto (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
It is undeniable that the current of westernization has been so strong. Western cultural values ​​and ideologies have entered the minds of most Indonesian Muslims. So unknowingly, he became a worldview. This study aims to examine two things; first. The importance of the Islamic worldview for a Muslim as a feature of his identity in the midst of globalization, and secondly. The role of Islamic education in building and linking the world view of Islam in Muslim societies in the midst of globalization. This research includes library research, so the data collection technique used in this research is literary data collection. The results of this study show that the Islamic worldview is very different from the western worldview regarding reality and truth because the Islamic worldview refers to the main sources, namely the Qur'an and Hadith. For this reason, the role and responsibility of Islamic education are to build and strengthen the worldview of Islam in Muslim society as a system of guidance and control over ideas and values ​​that undermine their identity or identity as Muslims. The education system must refer to the Islamic worldview to produce pious human beings who always base their attitudes and actions on Islamic teachings and values.